SOIL HEALTH ASSESMENT WITH CORNELL METHOD ON SOME PLANT PATTERN BY CORN AT KENAGARIAN MUNGKA - Fadil Hukama Hamdi; Juniarti Juniarti; Agustian Agustian; Ika Ayu Putri Septyani (Jurnal Agrotek Tropika, 2022)
Planted corn by intensively made decreased soil health and decreasing soil capacity to support plant growth caused of nutrient is not available, poor microbial activity, increasing soil acidity and soil crusting. If this problem do in long term, it will make decrease soil reciliency and decrease plant producitvity. This research was aim to investigate of soil health assesment with cornell method on some plant pattern by corn at Kenagarian Mungka. This research used explorative descriptive method through land survey and soil analyses in the laboratory. The samples were taken based on purposive random sampling. There were three land unit planted by corn with plant pattern are monoculture corn, corn-eggplant and corn-cassava. Each selected soil indicator scoring to discover the soil health correlation test to know relation between parameter with soil health.This research showed that Mungka’s land unit  planted by corn have moderate-high category for soil health, monoculture corn had the highest soil health by 65.96, corn-cassava had soil health value by 63.94 and the lowest is corn-eggplant with 63.35 soil health value. This research used three component of soil those are soil chemical, biology, and physic. This research showed that some indicator have the significant determinant indicator for soil health are OM (r=0,9209), pH (r=0,9471), and respiration (r=0,6055). Farmer was do the addition of organic matter from poultry manure to the land regularly. Based on this research, organic matter is the most important thing to keep soil health especially to encourage corn productivity.